MODERN METHODOLOGICAL APPROACH TO THE FORMATION OF CREATIVITY SKILLS OF STUDENT YOUTH (Western European Journal of Modern Experiments and Scientific Methods, 2024)
This article highlights the modern methodological approach to the formation of the creativity abilities of student youth, as well as the scientific ideas of specialists on communicative competence, as well as the importance of forming communicative competence in students in professional educational institutions